Video reportaje sobre la experiencia del banco de alimentos de Quito. - Cujilema Cujilema, Janeth Jacqueline (2016)
This communicative product was carried out with the objective of informing the public about the importance of preventing the perishable and non-perishable household food waste, which by any factor they shed them away on a daily basis. But after this problem, there are people who give a second chance to these products, it's the Food Bank, Foundation led by mothers of family and youth volunteers. They are responsible for 12 years of eliminating the waste of food in Quito. The process starts with a collection of foods on the wholesale market, located to the South of te capital. Place merchants donate their products to the Foundation since sometimes merchandise is not in good condition, but this is not a problem for the Bank. Later it underpinned is classified and placed in a wine of metallurgical industry of the National Polytechnic in San Bartolo, where Monday, Tuesday and Wednesday the families of limited resources registered in the project receive fruits and vegetables free. The Foundation also receives donations from companies that have products that are about to expire and may not be marketed. In this context the Bank gives the guarantee to be delivered the same day obtained for its consumed quickly. Currently, the Food Bank helps about 2,000 people of scarce resources this being a bridge between wealth and lack.